Kepimpinan Instruksional: Konsep, Model, Pendekatan dan Skala Pengukuran - Danielle, Foong Chai Yen; Mohd Khairuddin Abdullah (The Sultan Alauddin Sulaiman Shah Journal (JSASS), 2018)
Instructional leadership refers to any effort to encourage and support the parties involved in the process of teaching and learning to achieve the goals of the school and the establishment of an effective school social system. Three mainframe model of instructional leadership discussed in this article is a model Hallinger and Murphy, model Murphy and model Weber. There are nine aspects of educational leadership were identified by experts in education, which should be mastered by every principal who will manage and administer the school's management and organizational leadership, curriculum management, curriculum management, the management of the affairs of students, financial management, office administration, environmental management and physical facilities, management and development of human resources, management of external relations. Three scales of measurement used to assess the level of instructional leadership of the principal or head teacher is the Principal Instructional Management Rating Scale (PIMRS), The Leader Behavior Description Questionnaire (LBDQ) and the National Association of Secondary School Principals (NASSP). Hopefully this article can be used as a reference and adding a collection of literature related to instructional leadership or leadership teaching.